1999
DOI: 10.1029/1999ja900271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the vertical plasma drift velocity on the generation and evolution of equatorial spread F

Abstract: Abstract. We use radar observations from the Jicamarca Observatory from 1968 to 1992 to study the effects of the F region vertical plasma drift velocity on the generation and evolution of equatorial spread F. The dependence of these irregularities on season, solar cycle, and magnetic activity can be explained as resulting from the corresponding effects on the evening and nighttime vertical drifts. In the early night sector, the bottomside of the F layer is almost always unstable. The evolution of the unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
770
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(827 citation statements)
references
References 50 publications
55
770
2
Order By: Relevance
“…One of the basic requirements for the development of spread-F is the rapid uplifting of the F-layer to very high altitudes by the pre-reversal enhancement of zonal electric field in the post-sunset hours (Farley et al, 1970;Tsunoda and Ecklund, 2007). The evening vertical drift, or the pre-reversal electric field increases with solar flux (Abdu et al, 1983;Fejer et al, 1999), which could lead to greater rate of occurrence of ESF and EPB during the periods of higher solar activity (Sahai et al, 2000;Sobral et al, 2002). Growth rate for Perkins instability (Perkins, 1973), which is used to explain the generation of MSTID (Kelley and Fukao, 1991), is inversely proportional to ion-neutral collision frequency.…”
Section: Discussionmentioning
confidence: 99%
“…One of the basic requirements for the development of spread-F is the rapid uplifting of the F-layer to very high altitudes by the pre-reversal enhancement of zonal electric field in the post-sunset hours (Farley et al, 1970;Tsunoda and Ecklund, 2007). The evening vertical drift, or the pre-reversal electric field increases with solar flux (Abdu et al, 1983;Fejer et al, 1999), which could lead to greater rate of occurrence of ESF and EPB during the periods of higher solar activity (Sahai et al, 2000;Sobral et al, 2002). Growth rate for Perkins instability (Perkins, 1973), which is used to explain the generation of MSTID (Kelley and Fukao, 1991), is inversely proportional to ion-neutral collision frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Fejer et al [1999] derived a threshold upward plasma drift velocity necessary for the generation of plasma bubbles, and the threshold varies from $10 m s À1 at solar minimum to $40 m s À1 at solar maximum. Our observations are consistent with Fejer et al [1999]. However, the results of Fejer et al [1999] were derived from the measurements at a fixed longitude (Jicamarca).…”
Section: Discussionmentioning
confidence: 99%
“…This prereversal enhancement in the vertical plasma drift moves the F region to higher altitudes and increases the growth rate of the Rayleigh-Taylor instability, causing the occurrence of plasma bubbles. Fejer et al [1999] found that the upward plasma drift velocities necessary for the generation of equatorial spread F vary from $10 m s À1 near solar minimum to $40 m s À1 near solar maximum. Anderson et al [2004] found that equatorial plasma bubbles and resulting ionospheric scintillation occur, in general, when the vertical plasma drift is greater than 20 m s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have described a secondary maximum in ESF occurrence in the post-midnight period (Abdu et al, , 1983Fejer et al, 1999;Hysell and Burcham, 2002;MacDougall et al, 1998). During periods of high geomagnetic activity, electric fields can penetrate to low latitudes and cause the equatorial electric field to reverse in the post-midnight period, which is a source of ESF during periods of high geomagnetic activity (Kelley et al, 1979b;Fejer et al, 1999). Hysell and Burcham (2002) divides the pre-sunrise ESF into two categories.…”
Section: Equatorial Spread-fmentioning
confidence: 99%